A Prognostic Model of 15 Immune-Related Gene Pairs Associated With Tumor Mutation Burden for Hepatocellular Carcinoma - Huo, Junyu; Wu, Liqun; Zang, Yunjin (Frontiers in Molecular Biosciences, 2020)
Introduction: Tumor mutation burden(TMB) is an emerging biomarker for immunotherapy of hepatocellular carcinoma(HCC), but its value of clinical application has not been fully revealed. Materials and methods: We used wilcox test to identify the differentially expressed immune genes (DEIRGs) in groups with high and low TMB, respectively, as well as screened the immune gene pairs related to prognosis using univariate Cox regression analysis. A lasso Cox regression prognostic model was developed by combining the Cancer Genome Atlas (TCGA-LIHC) with International Cancer Genome Consortium (LIRI-JP) cohort, and internal(TCGA,ICGC) and external validation(GSE14520) was conducted on the predictive value of the model. We also explored the relationship between the prognostic model and tumor microenvironment via ESTIMATE algorithm and performed clinical correlation analysis by chi square test, and revealed its underlying molecular mechanism with the help of Gene Set Enrichment Analysis(GSEA). Results: The prognostic model consisted 15 immune gene pairs showed high predictive value for short-term and long-term survival of HCC in three independent cohort. Based on the univariate multivariate Cox regression analysis, the prognostic model could be used to independently predict the prognosis in each independent cohort. Group with a high risk held lower immune score, stromal score and estimate score values relative to group with a low risk. As shown by the Chi square test, the prognostic model exhibited an obvious correlation with the tumor stage (AJCC-TNM(p < 0.001), BCLC(p = 0.003)), histopathological grade(p = 0.033), vascular invasion(p =0.009), maximum diameter of tumor(p = 0.013) and background of liver cirrhosis(p <0.001). GSEA revealed that the group with a high risk saw the enrichment of many oncology features, inclusive of cell cycle, mismatch repair, DNA replication, RNA degradation, etc. Conclusion: Our research developed and validated a reliable prognostic model associated with TMB for HCC, which may help to enrich the therapeutic targets further of HCC.